2013
DOI: 10.4315/0362-028x.jfp-12-216
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Human Norovirus Surrogates: Murine Norovirus and Tulane Virus

Abstract: Viral surrogates are widely used by researchers to predict human norovirus behavior. Murine norovirus (MNV) is currently accepted as the best surrogate and is assumed to mimic the survival and inactivation of human noroviruses. Recently, a new calicivirus, the Tulane virus (TV), was discovered, and its potential as a human norovirus surrogate is being explored. This study aimed to compare the behavior of the two potential surrogates under varying treatments of pH (2.0 to 10.0), chlorine (0.2 to 2,000 ppm), he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
101
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 37 publications
10
101
1
Order By: Relevance
“…It's significant effect on infectious viral titre and genomic copy number confirms results of other studies which also revealed a significant effect on HuNoV genome integrity (Girard et al 2010;Lim et al 2010;Park and Sobsey 2011;Hirneisen and Kniel 2013;Tung et al 2013). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It's significant effect on infectious viral titre and genomic copy number confirms results of other studies which also revealed a significant effect on HuNoV genome integrity (Girard et al 2010;Lim et al 2010;Park and Sobsey 2011;Hirneisen and Kniel 2013;Tung et al 2013). …”
Section: Discussionsupporting
confidence: 87%
“…However Tulane virus does not belong to the genus Norovirus and is less resistant than MNV which is currently considered to be a better surrogate for HuNoV (Hirneisen and Kniel 2013). First isolated in 2003, MNV belongs to genogroup V and infects mice (Karst et al 2003;Wobus et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the importance of low-pH resistance and the need for relatively simple methods to allow the routine use of surrogates, FCV and PEC are inadequate for assessing the efficacies of methods to reduce the public health risk of norovirus infections. Based on our data and those of others, MNV and TuV are the most promising candidates for serving as surrogates for human norovirus (26). However, MNV is significantly more susceptible to alcohols than other nonenveloped viruses, as numerous studies have shown (19,20,22,43).…”
Section: Fig 7 Reductions In Tuv Infectivity and In Tuv And Human Normentioning
confidence: 99%
“…Many studies comparing FCV and MNV with or without other surrogates, such as MS2 coliphage and hepatitis A virus, as well as human norovirus (using reverse transcription-quantitative PCR [RT-qPCR]), have been published (4,(18)(19)(20)(21)(22)(23)(24). However, because MNV is highly sensitive to alcohols (18), the focus has expanded to cultivable calici-viruses such as TuV (14,(25)(26)(27)(28) and to porcine enteric calicivirus (PEC), a genogroup III (GIII) sapovirus (29,30).…”
mentioning
confidence: 99%
“…A challenge of rhesus monkeys with in vitro-cultivated TV resulted in intestinal infection with mild gastroenteritis, indicating that TV is an enteric pathogen (12). Because the TV also recognizes the HBGAs like NoVs (13), it has been used as a surrogate for human NoVs (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%